Traceability in Legal Pharmaceutical Supply Chains - ensuring safety and quality of prescribed medicinal products - Beckman, Catharina; Bernander, Emma (My University, 2015)
The legal pharmaceutical supply chains are today facing an increasing problem with counterfeit medicines worldwide. There are many documented cases where consumers have taken counterfeit medicines resulting in permanent injuries and even deaths. Supply chain traceability is fundamental to enable verification of authenticity for pharmaceutical products and to prevent counterfeit products to reach end consumers. The traceability is highly dependent on the supply chain actors' ability to share information. It is therefore of interest to study the information sharing in legal pharmaceutical supply chains to ensure safety and quality of medicinal products. The purpose of this master thesis is partly to present a framework to ensure safety of prescribed medicinal products in legal pharmaceutical supply chains. The aim is also to identify mandatory and voluntary information attributes that comply with legal and industrial safety requirements on information sharing. To fulfill the aim a case study was conducted. Multiple sources of data was collected; a survey, semi-structured interviews and internal documents. Eight companies and the Medical Products Agency, MPA participated in the case study. It was found that there is today no standard for identifying products in the studied supply chain and a variety of technologies and standards are used for exchanging data. Another finding was that the companies in the Swedish pharmaceutical supply chain are in harmony with the legislation provided by the MPA. The empirical findings were analyzed together with theory to identify important areas of improvement for enhancing the traceability, and thereby also the safety of medical products, in the pharmaceutical supply chain. The identified components for enhanced traceability are unique identification, standardized data carrier, standardized communication and guidelines for what information to share. These are visualized in the framework TracePharma. The theoretical contributions from this thesis are a comparison of published traceability frameworks within the food industry, and that the components identified in TracePharma can act as a starting point for further research. The practical implications are that the members of the pharmaceutical industry are provided with insight and understanding about how to improve the supply chain traceability and product safety. TracePharma can also be practically used for other supply chains, for example in other industries.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics